S1RS: an innovative and potential template for abstract and culturally grounded artworks - Mohamed Shaari, Zuriati; Mohamed Amin, Noor Hidawati; Arzain, Noriza; Ab Aziz, Nurul Izza; Abd Rahman, Siti Hajar (College of Creative Arts, 2025)
This study presents the development and verification of the S1RS abstract painting composition template, derived from the analysis of two reference artworks through three Gestalt principles: (i) symmetry, (ii) proximity, and (iii) closure. The template’s effectiveness is exemplified through the artwork S1RS: Kancil Membilang Buaya, conceptualized using Chang’s (2008) Autoethnography theory. The innovation has been recognized through exhibitions, awards, and art project grants, affirming its creative and academic value. Findings indicate that the S1RS template effectively generates abstract compositions while promoting and preserving Malay folktales through visual abstraction. This research and invention also aligns with Sustainable Development Goals (SDGs) 4 (Quality Education), 10 (Reduced Inequalities), and 11 (Sustainable Cities and Communities).